THE EFFECTIVITY OF ORAI APPLICATION IN TEACHING PRESENTATION SKILLS FOR NON-ENGLISH SENIOR HIGH SCHOOL TEACHERS - Kusumah, Cita Mustika; Novita, Dien (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2019)
Non-English teachers often get nervous and are not confident when they have to speak up in English, especially when they have to speak in front of many people or do the public speaking in English. But nowadays, there are many mobile applications that offer the new method in speaking English. Orai is one of the applications which concerns to help the users in improving their English-Speaking Skills. The research aims to examine the improvement of teachers’ speaking skills by using Orai application. The data were taken from the teachers who did not teach English in Senior High School in Bandung. Data were analyzed using descriptive statistic by finding out the total score per item. The results of the research show that Orai application helps teachers in improving their speaking skill. It helps teachers in correcting their pronunciation and their intonation when they speak. It also reduces some sources for the efficiency such as books, speakers, writing tools, headset, etc. The participants show the positive and good response using Orai application in assisting participants’ speaking fluency.